Complete elimination of hyperleukocytosis risk in AML through early high-quality disease remission - Lyu, Guoqing; Lyu, Wenting (Frontiers in Oncology, 2024)
Acute myeloid leukemia (AML) with hyperleukocytosis (HL) is a severe medical emergency associated with high mortality rates and poor prognosis. Prompt and urgent treatment is crucial to address this medical emergency. This study aims to elucidate appropriate diagnostic thresholds for HL and investigate underlying mechanisms and potential targeted therapies. To establish the HL threshold, the white blood cell (WBC) count was analyzed in adult AML patients. Contrary to the commonly accepted HL threshold of 100*109/L, our findings suggest that a HL threshold of 75*109/L is more appropriate. This lowed threshold will help guide clinicians in identifying more patients requiring immediate intervention. Additionally, significant correlations were observed between HL and specific mutations, including NPM1, FLT3, DNMT3A. In pediatric AML patients, the HL threshold for WBC count was determined to be 165*109/L. Achieving high-quality early disease remission effectively eliminated HL risks, highlighting the importance of swift intervention. Therefore, proactive treatment in the early stages of leukemia is essential to achieve high-quality deep remission and minimize the risk of HL. Understanding the underlying mechanisms of HL remains a challenge, differential gene expression analysis implicated downregulation of cell adhesion molecules in HL pathogenesis. Potential molecular targeted drugs for AML with HL include Bcl2 inhibitors and histone deacetylase inhibitors. Clinical observations have shown that the addition of Bcl2 inhibitors, such as Venetoclax, to standard therapy leads to a rapid reduction in WBC count, effectively reducing tumor burden and providing prompt symptom relief. Combining these molecular targeted drugs with conventional therapies shows promise as an excellent treatment approach to mitigate risks for patients. For future treatments targeting this high-risk hematological emergency, the combination of additional molecular targeted drugs with conventional therapies should be considered to improve patient outcomes.